“Water-in-montmorillonite” quasi-solid-state electrolyte for ultralow self-discharge aqueous zinc-ion batteries - Yongfeng Huang; Rongsheng Guo; Yunlin An; Wenbao Liu; Feiyu Kang (Energy Materials and Devices)
The practical application of aqueous zinc-ion batteries (AZIBs) is limited by zinc dendrites, parasitic reactions, and self-discharging. Quasi-solid-state electrolytes (QSSEs) are promising solutions but have high costs, low conductivity, and inadequate self-discharge-suppression capability. This study introduces a novel “water-in-montmorillonite (Mont)” (WiME) electrolyte to address these limitations. WiME leverages the layered structure of the inexpensive Mont to confine water, achieving a high ionic conductivity of 64.82 mS/cm and remarkable self-discharge suppression capability and maintaining 92.7% capacity after 720 h. The WiME architecture facilitates uniform Zn deposition and promotes cycling stability at high current densities. WiME-based symmetric cells show excellent long-term cycling, surpassing 1900 h, and full Zn||MnOOH cells display stable cycling for 500 cycles without capacity decay, demonstrating synergy among mitigated parasitic reactions, homogenous zinc deposition, and enhanced interfacial stability enabled by WiMEs. This study presents a low-cost and high-performance strategy for advancing the practical application of AZIBs for various fields.